Strategi Menggali Potensi Siswa Melalui Kegiatan Lomba Gebyar Islami dalam Program Pengalaman Lapangan di SMPN 1 Bojong - eka 'ainiyyah, cita; Nadlifah, Izzatun; Aulia, Nurul; Alfina Maulidia, Rahma; Riyadi, Dimas; Hami, Widodo (Al-Nizam: Indonesian Journal of Research and Community Service, 2025)
This study aims to describe strategies for exploring students’ potential through the “Gebyar Islami” religious competition organized by the Field Experience Practice (PPL) students of UIN K.H. Abdurrahman Wahid Pekalongan at SMP Negeri 1 Bojong. This research employed a descriptive qualitative approach focusing on three main aspects: the role of PPL students in organizing the event, the implementation strategies used to uncover students’ potential, and the challenges and solutions encountered during the process. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The results show that the “Gebyar Islami” event consisting of Qur’an recitation (tartil), calligraphy, and nasheed competitions was effective in building students’ confidence, facilitating the expression of their religious talents, and strengthening their spiritual and social character. Challenges such as communication gaps among committees were successfully resolved through coordination and deliberation. Overall, the program provided significant benefits for students, teachers, and PPL participants as a means of developing student potential and applying Islamic education theory in real contexts.